Report on a Group's Reaction to: “The Researcher and the Manager: A Dialectic of Implementation” - Ladd, Donald E. (Management Science, 1965)
On April 5, 1965 the members of a class in Studies in Operations Research were presented with statements (appended) concerning the relationship of the scientist in industry with the industrial manager. There were four such statements, presented in written form, one at a time and in orders which differed for each individual. For each statement, the members were asked only to note whether they agreed or disagreed.